中国中产阶级与留学热 ：以教育观探讨其关系 = The China’s middle class and the trend of overseas education : investigation of the relationship through the view on education - Ho, Keith Song Xiang (2017)
The China’s middle class is an emerging social class arising from the Chinese economic reform. Academia has different interpretations with regards to the composition of the middle class. The developing Chinese middle class consist of a wide variety of people, which includes the highly educated white-collar workers and the lowly educated blue-collar workers. Although the composition of the Chinese middle class is complex, they share the same expenditure behaviour – setting their child’s education as their priority. This group of people fulfill the view on education of their child through their economic ability. Their view on education consists of various factors such as the collision of traditional and realistic ideas, the prevalence of the degree-chasing phenomenal and the inheritance and transformation of cultural capital. As the trend of overseas education continues to rise in the Chinese society, it is evident that the middle class takes up a large proportion of the group chasing after this trend. Their reason for choosing overseas education stem from their view on education which is affected by both the internal push factor in China and the external pull factor from overseas. As such, this paper seeks to examine the relationship between the China’s middle class view on education and the trend of overseas education. Keywords: China’s Middle Class, View on Education, Expenditure Behaviour, Overseas Education, Relationship 中国的中产阶级是改革开放以来形成的一个新兴社会阶层。对于中产阶级的构成，学术界有不同的解释。其中在处于发展状态的中国中产阶级，不仅包括受过高等教育的白领人士，也有一大群不但没有文凭还从事蓝领工作的人士。虽然此阶层的构成相当复杂，可是他们持有着相同的以子女教育为优先的消费行为。